2021
DOI: 10.1029/2021jb021991
|View full text |Cite
|
Sign up to set email alerts
|

Hypocenter Hotspots Illuminated Using a New Cross‐Correlation‐Based Hypocenter and Centroid Relocation Method

Abstract: Accurate earthquake locations are important for understanding earthquake processes. Recent advances in earthquake relocation methods have resulted in relative centroid locations with smaller uncertainties using cross‐correlation‐based methods. However, relative hypocenter locations, which are traditionally determined using the onset times of event waveforms, generally possess larger uncertainties than that of the centroids. Here, we develop a new cross‐correlation‐based relative hypocenter relocation method ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the Mw5-6 quasi-repeating earthquake source regions, M2-3 repeating earthquakes also occurred (Figures 6a and 6b), forming a hierarchical structure. M2-3 repeating earthquakes occurred inside the source regions of the Mw5-6 repeating earthquakes near the hypocenter of the March Mw7.0 event (Figure 6), showing that seismic patches in this region form a hierarchical structure like that formed by the Kamaishi repeating earthquakes and others (Chang & Ide, 2021;Ide, 2019;Okuda & Ide, 2018;Uchida et al, 2007).…”
Section: Aseismic-to-seismic Transition After the Tohoku Earthquake A...mentioning
confidence: 98%
“…In the Mw5-6 quasi-repeating earthquake source regions, M2-3 repeating earthquakes also occurred (Figures 6a and 6b), forming a hierarchical structure. M2-3 repeating earthquakes occurred inside the source regions of the Mw5-6 repeating earthquakes near the hypocenter of the March Mw7.0 event (Figure 6), showing that seismic patches in this region form a hierarchical structure like that formed by the Kamaishi repeating earthquakes and others (Chang & Ide, 2021;Ide, 2019;Okuda & Ide, 2018;Uchida et al, 2007).…”
Section: Aseismic-to-seismic Transition After the Tohoku Earthquake A...mentioning
confidence: 98%
“…Seafloor topography is from Smith and Sandwell (1997). The plate motion is based on Bird (2003) Nishikawa et al Progress in Earth and Planetary Science (2023) 10:1 investigated in detail (e.g., Okada et al 2003;Uchida et al 2007;Okuda and Ide 2018;Ide 2019a;Chang and Ide 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The small amount of slip accommodated by partial ruptures is observed in Parkfield and potentially in other areas with repeating earthquakes. Chang and Ide (2021) studied three repeating patches in Japan that experienced hierarchical ruptures, which we refer to as partial ruptures. The moment in the reported smaller magnitude events that are observed is only 1%–23% of the total sequence moment, which aligns with what we have observed in Parkfield.…”
Section: Discussionmentioning
confidence: 99%
“…Such inter‐repeater slip seems plausible—recent studies have observed “hierarchical rupture distributions” of repeating earthquakes in Japan, whereby the ruptures of small earthquakes are located within the rupture areas of larger repeating events (Chang & Ide, 2021; Ide, 2019; Okuda & Ide, 2018; Uchida et al., 2007). If the ruptures of a given patch followed a Gutenberg‐Richter distribution that extended to a maximum magnitude equal to the repeater magnitude, each magnitude 3 repeater should be accompanied by 10–20 observable partial ruptures.…”
Section: Introductionmentioning
confidence: 99%